Ethnopharmacological Applications Targeting Alcohol Abuse: Overview and Outlook - Singh, Laxman; Joshi, Tanuj; Tewari, Devesh; Echeverría, Javier; Mocan, Andrei; Sah, Archana N.; Parvanov, Emil; Tzvetkov, Nikolay T.; Ma, Zheng Feei; Lee, Yeong Yeh; Poznański, Piotr; Huminiecki, Lukasz; et al. (Frontiers in Pharmacology, 2020)
Excessive alcohol consumption is the cause of several diseases and thus is of a major concern for society. Worldwide alcohol consumption has increased by many folds over the past decades. This urgently calls for intervention and relapse counteract measures. Modern pharmacological solutions induce complete alcohol self-restraint and prevent relapse, but they have many side effects. Natural products are most promising as they cause fewer adverse effects. Here we discuss in detail the medicinal plants used in various traditional/folklore medicine systems for targeting alcohol abuse. We also comprehensively describe preclinical and clinical studies done on some of these plants along with the possible mechanisms of action.